Special Issue “International Conference of Spirituality in Healthcare. Creating Space for Spirituality in Healthcare,”—Trinity College Dublin 2017 - Kathleen Neenan; Fiona Timmins; Colm O. Boyle; Jacqueline Whelan; Vivienne Brady; Yvonne Muldowney; Wilfred McSherry (Religions, 2019)
This is an editorial of a Special Issue pertaining to the “International Conference of Spirituality in Healthcare. Creating a Space for Spirituality in Healthcare” Trinity College Dublin 2017. This was the third International Spirituality in Healthcare Conference hosted by Trinity College Dublin, with future annual conferences planned. This conference has provided a space to facilitate clinicians, healthcare practitioners and academics to present and debate current issues with this domain. This editorial summarises some of the papers that have been published arising from that conference.